ANALYSIS OF WORK MOTIVATION IN IMPROVING EMPLOYEE PERFORMANCE AT THE BUMI JAYA OIL PALM PLANTATION VILLAGE UNIT COOPERATIVE, TELUK GELAM DISTRICT, OKI REGENCY - Supriadi, Supriadi; Prima, Aldi; Marjohan (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2022)
This study entitled